2017
DOI: 10.1007/s00436-017-5461-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, investigator-blinded, controlled clinical study with lice shampoo (Licener®) versus dimethicone (Jacutin® Pedicul Fluid) for the treatment of infestations with head lice

Abstract: The present clinical trial was conducted to obtain additional data for the safety and efficacy of a head lice shampoo that is free of silicone compared with an anti-head lice product containing dimethicone. Both products act by a physical mode of action. This randomized, investigator-blinded, controlled clinical study was conducted between July and November 2016 in households of two villages (Abou Rawash and Shandalat) in Egypt. Children older than 2 years with an active head lice infestation were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Additionally, Arslan et al 39 reported a genotoxic and cytotoxic potential for mixtures containing piperonyl butoxide. Our results agree with a previous report 32 that revealed the decreased safety and efficacy of medical treatments for head lice. Meister and Ochsendorf 40 observed the decreasing efficacy of permethrin and reported the successful treatment of head lice with ovicidal dimethicones.…”
Section: Medical Treatments Of Infected Studentssupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, Arslan et al 39 reported a genotoxic and cytotoxic potential for mixtures containing piperonyl butoxide. Our results agree with a previous report 32 that revealed the decreased safety and efficacy of medical treatments for head lice. Meister and Ochsendorf 40 observed the decreasing efficacy of permethrin and reported the successful treatment of head lice with ovicidal dimethicones.…”
Section: Medical Treatments Of Infected Studentssupporting
confidence: 94%
“…A comparison with the surrounding and international countries, revealed the prevalence of head lice in children from kindergarten and schools from Israel 27 , children from schools in Egypt 9 , children from schools in Saudi Arabia 28 , children from schools in Iran 21 , children from Jordan 29 , children from the UK 30 , USA 31 and Germany 32 . However, the prevalence among international and/or surrounding countries is quite different due to different educational levels, medical care, weather and living conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Dimethicone can be used in children more than 2 years of age. Furthermore, after 1 day of treatment with 100% dimethicone, 98.3% of subjects were free of live lice 9,10 . Dimethicone avoids pesticide exposure and resistance issues, 11 but the mechanism of action remains unclear 7 because head lice are reported to live in anoxic conditions for 8–14 h 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, after 1 day of treatment with 100% dimethicone, 98.3% of subjects were free of live lice. 9,10 Dimethicone avoids pesticide exposure and resistance issues, 11 but the mechanism of action remains unclear 7 because head lice are reported to live in anoxic conditions for 8-14 h. 12 In addition, the expansion of kdr mutations in head lice has been reported in Denmark 13 and Mexico. 14 Hence, effective therapeutic strategies against infestations need to be established.…”
Section: Introductionmentioning
confidence: 99%
“…There is a tendency to shorten the application time in order to increase treatment compliance. Application times as short as 10 min have been described to be effective for products based on mineral oil [24] and neem seed extract [25]. Given the high socio-economic and psycho-social burden of head louse infestations, effective, reliable, safe and rapid treatment options are needed.…”
Section: Introductionmentioning
confidence: 99%